Extra-territorial nation-building in flows and relations: North Korea in the global networks and an ethnic enclave. (October 2019) - Shin, HaeRan
Abstract: This study looks at how North Korean transnational refugees' discourses and practices constitute a new version of the nation outside the materially bordered geography of their homeland. The research suggests the notion of 'extra-territorial nation-building' that refers to the social and cultural practices that build a nation as a collective identity and imagined society outside the national territory. Previous studies have not done enough to distinguish the nation from the state, and neither have they acknowledged the importance of individual agents involved in bottom-up nation-building. I focus particularly on the political and social engagement of North Korean refugees who first found refuge in South Korea and then emigrated to the United Kingdom. Based on ethnographic fieldwork including participant observation and in-depth interviews, the findings of the study are twofold. First, it establishes how the global network of North Korean refugees contributed to extra-territorial nation-building through the flow of ideas, discourses, and activities. These efforts also aided in envisioning a future version of the North Korean nation proper as network members collaborated to initiate measures that would establish an exile government and political activities. Second, nation-building efforts in relations were vital in distinguishing the North Korean identity from South Korean and Korean-Chinese migrants. As North Koreans resisted integration and adopting South Korean customs, they founded a North Korean language school for their second and third generations, a North Korean association, and cultural organisations so that their community in essence became their nation. This research contributes to the understanding of post-territorial and relational approaches as they apply to the concept of the nation.